DIFFERENCES OF IDEAS UNDER THE INFLUENCE OF SOCIO-POLITICAL PROCESSES IN SOCIETY (Web of Teachers: Inderscience Research, 2024)
It is a holistic doctrine that was formed in the years of independence, has its own philosophical basis, scientific-theoretical and historical roots. This doctrine expresses the goals and aspirations of our people, who are building a free and prosperous Motherland, a free and prosperous life, as an objective necessity of the country's development, a legitimate product of national development.